Distracted pedestrian behavior: An observational study of risk by situational environments. (28th June 2022) - Schwebel, David C.; Canter, Margaret F.; Hasan, Ragib; Griffin, Russell; White, Taylor R.; Johnston, Anna
Abstract: Objective: Pedestrian-related death rates are increasing in the United States, partly due to increased use of distracting smartphones by pedestrians. Previous research documents high frequency of smartphone use while crossing streets near college campuses and in downtown business districts, but little is known about distracted pedestrian behavior in other urban environments. The current study used observational methods to examine and compare distracted pedestrian behavior in four urban areas – near an urban college campus, in a downtown commercial business district, near middle and high schools, and in entertainment districts – as well as examining whether the occurrence of distraction was associated with unsafe crossing behaviors. Methods: We observed 112 intersections in 46 downtown, 30 school, 25 entertainment district, and 11 college campus-area intersections. Coders recorded distraction, crossing safety, pedestrian demographics, and traffic volume. Chi-square tests compared pedestrian characteristics by intersection type. Log binomial regressions estimated risk ratios (RRs) and associated 95% confidence intervals (CIs) for associations between pedestrians walking alone and traffic volume with distracted crossing behavior, adjusting for age and gender. Similar models examined risk of unsafe crossing behavior by distraction behavior. All models were stratified by intersection type. Results: Distraction incidence was highest in campus locations (52.9%) and lowest in entertainment districts (16.2%). Walking alone was associated with a 45% higher risk of distraction (RR 1.45, 95% CI 1.30-1.62), although the increased association was limited to entertainment locations (RR 1.61, 95% CI 1.25-2.08) and was significantly decreased in all other locations. Higher traffic volume was associated with lower risk of distraction in downtown locations (RR 0.69, 95% CI 0.56-0.85) but higher distraction risk in entertainment locations (RR 1.71, 95% CI 1.27-2.31). Associations between distraction and unsafe crossing behaviors were minimal. Conclusion: Distracted pedestrian behavior occurs at different rates and in different circumstances, depending on the setting. These results offer valuable data to inform intervention programs that target appropriate populations in appropriate locations.